The sufficiency of the beneficiary in the rulings of imitation of the scholar Khalifa Al-Safti Al-Shafi’i Al-Masry (d.: 1293 AH) from the beginning of the manuscript to his saying Benefit Al-Subki said: “The transmission from one school of thought to another study and investigation - Ali Jassim Al-Shafei, Mahmoud Hussein (Journal of Tikrit University for Humanities, 2023)
This is a brief treatise on the fundamentals of jurisprudence by the scholar Sheikh Khalifa Al-Safti, may God Almighty have mercy on him, in which he explained briefly and in an easy and clear style, what is related to ijtihad and imitation, and may God Almighty have mercy on him in this message was distinguished by his wonderful style that reaches the mind of the reader in the shortest way, and this is only possible for him who reached To a high rank in science, and an amazing ability to employ information in a clear graphic template, with the ease and brevity of the phrase, and its fulfillment of the intended, and this is what the reader will notice in this brief message. Despite its small size and lack of papers, this treatise contains all the vocabulary related to an important fundamental topic, which is ijtihad and imitation. The author began presenting the scientific material by saying: a question, a branch, a benefit, or a warning, so he mentioned the first issue and opened his message with it, which is the absolute mujtahid, so he clarified what the fundamentalists wanted with it, then whoever falls short of this rank must imitate others who have reached this scientific rank, and he indicated that the mufti Either he is one of the people of absolute ijtihad, or the mujtahid of the madhhab, or one of the people of faces, and whoever does not reach these ranks, then he named him a narrator or informer of the madhhab, and elaborated in detail in explaining the meaning of each of these four ranks. In the folds of the manuscript, he talks about the judge, the mufti, the sections of the mufti, and the issues related to the questioner, and singles out those who imitate our master Imam Al-Shafi’i, may God’s prayers be upon him, and that it is not permissible for him, if there are two opinions in the matter, to choose from them, but rather he must search for the most correct of them, and that it is permissible to judge and issue fatwas in any of the schools of thought. Islamic doctrines; Because the scholars of the doctrine have based their doctrines on solid scientific principles, refined them, revised them, and verified them, and God Almighty preserved them from extinction, and the importance of the manuscript comes from the scientific material and the fundamental and subsidiary issues that it dealt with. For all of this, may God Almighty grant me success to achieve this letter in two written copies written during the life of the author, and at the hands of his students, and I tried to extract the verified text intact from distortion and omission, taking into account the rules of spelling in our current time, with comments that I think are useful in their section.